No Association between the 20210 G/A Prothrombin Gene Mutation and Premature Coronary Artery Disease - Eikelboom, J. W.; Baker, R. I.; Parsons, R.; Taylor, R. R.; van Bockxmeer, F. M. (Thrombosis and Haemostasis, 1998)
The 20210 G/A prothrombin gene mutation is associated with an increased risk of venous thrombosis but whether there is an association of the mutation with premature coronary artery disease and acute myocardial infarction remains unclear.To further assess the role of the G/A genotype as a risk factor for arterial vascular disease, we performed a case-control study of 644 patients aged less than 50 years with angiographically proven coronary artery disease, 402 of whom had myocardial infarction, and 679 unrelated healthy control subjects aged less than 50 years, randomly selected from the electoral roll.The prevalence of the G/A genotype was 2.5% in patients with coronary artery disease, and 3.2% in control subjects (odds ratio 0.8; 95% confidence interval 0.35 to 1.83). The mutation was not more frequent among patients with a history of myocardial infarction (2.2%, odds ratio 0.7; 95% confidence interval 0.27 to 2.05), and there was no evidence of an interaction between the prothrombin mutation and conventional cardiovascular disease risk factors. There was no association between genotype and extent of angiographic coronary artery disease (p = 0.73).We conclude that the 20210 G/A prothrombin gene mutation is not a major risk factor for premature coronary artery disease in our predominantly Caucasian Australian population.